Persepsi Mahasiswi Program Intensif Terhadap Kedisiplinan Belajar Di IDIA - Fayruzah El-Faradis; Nirfa Nirfa (Moral : Jurnal kajian Pendidikan Islam, 2025)
The focus of research are : 1. What are the Perceptions of Intensive Program Students towards Study Discipline at IDIA 2. What are the Supporting and Inhibiting Factors for Learning Discipline at IDIA in the Intensive Program. In this research, researcher used a qualitative approach. The data collection method in this research uses interviews and documentation. And the informants in this research came from Mudir Ma'had Lil-Banat, Naibah Mudir Ma'had Lil-Banat, academic section teacher, Student Executive Council Boarding Ma’had (BEMA), and IDIA intensive program students. The perception of intensive program students towards the learning discipline at IDIA is very positive. This can be seen from the different opinions and expressions in expressing perceptions about learning discipline at IDIA in the intensive program. Supporting factors for learning discipline in the intensive program at IDIA are the existence of clear regulations, the professionalism of internship teachers, and the existence of good and strong cooperation between internship teachers and BEMA. Meanwhile, the inhibiting factors are the different characters or dispositions of intensive program students, teachers/instructors who cannot be present while teaching, and limited learning environment.